Interactive Metadiscourse in Arabic Abstracts: A Comparative Study of Kitābah Implications for Native and Non-Native Writers - Siti Nursa'adah; Syihabuddin; Rinaldi Supriadi (IAIN Madura, 2026)
This study investigates the use of interactive metadiscourse in Arabic research article abstracts, with particular attention to rhetorical differences between native Arab writers and non-native Indonesian writers. Metadiscourse in abstracts is crucial, as it shapes textual clarity, coherence, and the perceived credibility of scholarly work. Drawing on Hyland’s framework of interactive metadiscourse, this study analyzed forty Arabic research article abstracts, consisting of twenty abstracts written by native Arab authors and twenty by non-native Indonesian authors. The data were coded using a structured codebook and quantitatively analyzed to examine the distribution of interactive metadiscourse categories across both groups. The findings reveal significant rhetorical differences. Non-native writers tend to employ interactive metadiscourse more explicitly to signal research purposes, stages, and logical relations, while native writers rely more heavily on implicit cohesion, reflecting established Arabic rhetorical conventions. These patterns indicate that cultural and academic backgrounds play an important role in shaping abstract writing practices. By situating these findings within the perspective of contrastive rhetoric, this study extends existing metadiscourse research and provides pedagogical implications for improving kitābah instruction for non-native learners of Arabic.